FRI0355 Treatment and outcome of ANCA-associated vasculitis in children: A pilot study. (23rd January 2014) - Twilt, M.; Bell-Peter, A.; Laxer, R.; Pagnoux, C.; Hebert, D.; Harvey, E.; Sheikh, S.; Benseler, S.M.
Abstract : Background: Childhood ANCA vasculitides are rare, yet organ- or even life-threatening systemic vasculitides. Children most frequently present with rapidly evolving, severe disease such as pulmonary-renal syndrome. In 2009, evidence-based EULAR treatment recommendations were published. Treatment efficacy and safety data are largely derived from adult studies. Objectives: To report treatment efficacy and safety of the 2009 EULAR recommendations for severe-moderate disease onset in consecutive pediatric patients with newly diagnosed ANCA vasculitides. Methods: A single-center cohort study of consecutive children newly diagnosed with ANCA vasculitis since July 2010 was performed. All children were treated according to the implemented EULAR recommendations. Baseline clinical and laboratory characteristics, treatment regimens and their efficacy and safety were analysed. Disease activity was documented using the Pediatric Vasculitis Activity Score (PVAS). Adverse and serious adverse events and disease damage were captured. Results: A total of 8 children (4 female, 4 male) were included, median age at diagnosis was 13.8 years (range 10.9-17.4 years); presenting clinical features were nephritis in 7 (including renal failure in 2) and lung disease in 4 (including pulmonary hemorrhage in 3), ENT involvement in 3 (including subglottic stenoses in 2), and eye disease in 3 (1 episcleritis). Laboratory investigation: median ESR was 72mm/h, CRP 99mg/dl. ANCA testing was positive in 7 children (6 c-ANCA, +PR3, 1 p-anca, +MPO). All patients were treated with high dose prednisone, with a tapering scheme, and iv cyclophosphamide pulses, 4/8 received additional plasmapheresis (PLEX) (3 for pulmonary renal syndrome - 1 for renal failure). Seven children completed the induction therapy and were commenced on Azathioprine, with low-dose prednisone for maintenance. Disease activity at diagnosis: median PVAS was 19 (14-29); Follow-up PVAS: 3 (1-5) at 3 month and 3 (1-3) at 6 months. One child presented in renal failure and remains on dialysis. Safety: 50% of the PLEX-treated children developed a central line clot and subsequent pulmonary embolism requiring long-term anticoagulation. No clots were seen in patients not treated with PLEX. Clots are a known complication of central lines though. Pulmonary blastomycosis was confirmed in one child receiving PLEX and cyclophosphamide, who presented with a single lung nodule at 3 months of treatment. She responded rapidly to anti-fungal therapy. No early disease flares were noticed during the follow-up. Conclusions: A significant decrease in disease activity was seen in all children with newly diagnosed, severe ANCA vasculitis treated according to the EULAR recommendations (PVAS 19 to 3). An increased risk of clots was seen in children treated with adjunctive plasmapheresis. References: Mukhtyar C, et al. EULAR recommendations for the management of primary small and medium vessel vasculitis. Ann Rheum Dis 2009;68(3):310-17 Disclosure of Interest: None Declared